Effect of the nanowire diameter on the linearity of the response of GaN-based heterostructured nanowire photodetectors. (25th April 2018) - Spies, Maria; Polaczyński, Jakub; Ajay, Akhil; Kalita, Dipankar; Luong, Minh Anh; Lähnemann, Jonas; Gayral, Bruno; den Hertog, Martien I; Monroy, Eva
Abstract: Nanowire photodetectors are investigated because of their compatibility with flexible electronics, or for the implementation of on-chip optical interconnects. Such devices are characterized by ultrahigh photocurrent gain, but their photoresponse scales sublinearly with the optical power. Here, we present a study of single-nanowire photodetectors displaying a linear response to ultraviolet illumination. Their structure consists of a GaN nanowire incorporating an AlN/GaN/AlN heterostructure, which generates an internal electric field. The activity of the heterostructure is confirmed by the rectifying behavior of the current–voltage characteristics in the dark, as well as by the asymmetry of the photoresponse in magnitude and linearity. Under reverse bias (negative bias on the GaN cap segment), the detectors behave linearly with the impinging optical power when the nanowire diameter is below a certain threshold (≈80 nm), which corresponds to the total depletion of the nanowire stem due to the Fermi level pinning at the sidewalls. In the case of nanowires that are only partially depleted, their nonlinearity is explained by a nonlinear variation of the diameter of their central conducting channel under illumination.